2014
DOI: 10.1111/1756-185x.12389
|View full text |Cite
|
Sign up to set email alerts
|

Do male and female patients with chronic neck pain really have different health‐related physical fitness, depression, anxiety and quality of life parameters?

Abstract: We suggest that, on the basis of gender, consideration of not only the neck region but also whole body physical fitness, anxiety and depression parameters in patients with CNP might be helpful to the development of more benefical strategies for illness management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 42 publications
3
38
1
Order By: Relevance
“…Patients with chronic neck pain often present with a variety of other signs and symptoms. These may include physical impairments as decreased cervical mobility and altered neuromuscular function of the flexor [2] and extensor [3] muscles, as well as psychological distress, depression and fear avoidance [4], and reduced quality of life [5]. The extent of some of these factors may depend on the origin of pain with differences observed between those with traumatic versus non-traumatic neck pain [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic neck pain often present with a variety of other signs and symptoms. These may include physical impairments as decreased cervical mobility and altered neuromuscular function of the flexor [2] and extensor [3] muscles, as well as psychological distress, depression and fear avoidance [4], and reduced quality of life [5]. The extent of some of these factors may depend on the origin of pain with differences observed between those with traumatic versus non-traumatic neck pain [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relationship between the mass of trunk muscle, including skeletal muscle, and low back pain has also attracted attention. Some researchers have reported an association of body composition with musculoskeletal pain and have demonstrated that a greater fat mass and an attenuated muscle mass were associated with increased musculoskeletal pain 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that, in patients with chronic neck pain, consideration of not only the neck region but also the whole body physical fitness, and also anxiety and depression parameters might be more beneficial for the management strategies (Yalcinkaya et al, 2014). In this context, chronic MNP has been addressed with a variety of interventions including heat, traction, laser, manual therapy, and exercise (Sherman et al, 2009;Miller et al, 2010;Graham et al, 2013).…”
Section: Introductionmentioning
confidence: 99%